Patient preferences for treatment in steroid resistant ulcerative colitis – a discrete-choice experiment. (3rd July 2022) - Wickramasekera, Nyantara; Coates, Elizabeth; Barr, Amy; Lee, Matthew J.; Blackwell, Sue; Bedford, Hugh; Dames, Nicola; Sebastian, Shaji; Probert, Christopher; Shackley, Phil; Lobo, Alan J.
Abstract: Background and aim: Understanding treatment preferences in those patients who are not responding to corticosteroids for ulcerative colitis is important in informing treatment choices. This study aimed to assess the relative importance of treatment characteristics to patients by conducting a discrete-choice experiment. Methods: Patients completed the questionnaire online. All data were collected between September and December 2020. Participants were shown 13 discrete-choice experiment tasks – a series of side-by-side comparisons of competing, hypothetical treatment characteristics and asked to select a preferred treatment. Survey responses were analysed using descriptive statistics and regression analyses. Results: 115 patients completed the study. Patient preferences were strongest for treatments with a lower chance of side effects, this attribute had the most influence on the choice of treatment patients preferred. The second most important attribute was an improvement in maintaining remission. Conversely, route and frequency of administration were least important on the choice of treatment patients preferred. Respondents were willing to make trade offs and accept treatment benefits to compensate them for receiving a treatment with a less desirable attribute level. Participants were willing to accept a larger benefit of 45% improvement in maintenance of remission to accept a treatment with a higher probability of side effects. The benefit required was smaller with a 10% improvement in remission required to accept a treatment with a lower probability of side effects. Conclusion: Quantifying preferences helps to identify and prioritise treatment characteristics that are important to patients. The results highlight the importance of careful discussion of side effects, including the magnitude of risk, using visualisation tools during a patient consultation to support decisions.